Proceedings From the Society for Advancement of Blood Management Annual Meeting 2017: Management Dilemmas of the Surgical Patient—When Blood Is Not an Option. Issue 3 (September 2019) - Tan, G.M.; Guinn, G.R.; Frank, S.M.; Shander, A.
Abstract : ( Anesth Analg . 2019;128:144–151) It is well established that blood loss >500 mL and/or hemoglobin (Hb) <5 g/dL are both associated with increased morbidity and mortality. Fortunately, perioperative bleeding is a known preventable complication, and procedures that are at increased risk of severe blood loss are well recognized (eg, obstetric, cardiothoracic, spine, and cancer surgeries). However, there are cases in which patient blood management (PBM) is complicated by religious or medicolegal issues. Therefore, in this special article, authors discuss PBM approaches in cases where blood transfusion is not an option (religious, inability to find blood matches, or lack of resources due to location).